Isolation, characterization, and application of a novel polyvalent lytic phage STWB21 against typhoidal and nontyphoidal Salmonella spp. - Mondal, Payel; Mallick, Bani; Dutta, Moumita; Dutta, Shanta (Frontiers in Microbiology, 2022)
Salmonella is one of the common causal agents of bacterial gastroenteritis-related morbidity and mortality among children below five years and the elderly populations. Salmonellosis in humans is caused mainly by consuming contaminated food originating from animals. The genus Salmonella has several serovars, and many of them are recently reported to be resistant to multiple drugs. Therefore, isolation of lytic Salmonella bacteriophages in search of bactericidal activity has received importance. In this study, a Salmonella phage STWB21 was isolated from a lake water sample and found to be a novel lytic phage with promising potential against the host bacteria Salmonella typhi. However, some polyvalence was observed in their broad host range. In addition to S. typhi, the phage STWB21 was able to infect S. paratyphi, S. typhimurium, S. enteritidis, and a few other bacterial species such as Sh. flexneri 2a, Sh. flexneri 3a, and ETEC. The newly isolated phage STWB21 belongs to the Siphoviridae family with an icosahedral head and a long flexible non-contractile tail. Phage STWB21 is relatively stable under a wide range of pH (4-11) and temperatures (4°C-50°C) for different Salmonella serovars. The latent period and burst size of phage STWB21 against S. typhi were 25 min and 161 plaque-forming units per cell. Since Salmonella is a foodborne pathogen, the phage STWB21 was applied to treat a 24 h biofilm formed in onion and milk under laboratory conditions. A significant reduction was observed in the bacterial population of S. typhi biofilm in both cases. Phage STWB21 contained a dsDNA of 112,834 bp in length, and the GC content was 40.37%. Also, genomic analysis confirmed the presence of lytic genes and the absence of any lysogeny or toxin genes. Overall, the present study reveals phage STWB21 has a promising ability to be used as a biocontrol agent of Salmonella spp. and proposes its application in food industries.